Between Praise and Criticism: A Sentiment Analysis of Kang Dedi Mulyadi's Leadership On X (Twitter) - Achwan Noorlistyo Adi; Diwan Setiawan; Eny Ratnasari (Kirana Publisher (KNPub), 2026)
Twitter, an archetypal example of an open and real-time social media platform, has emerged as a pivotal virtual interaction space, particularly in the context of shaping public opinion, particularly with regard to political figures. The objective of this study is to analyze the sentiments expressed by netizens regarding the leadership of Governor of West Java, Kang Dedi Mulyadi, through the implementation of sentiment analysis. The data was obtained by utilizing Tweet Harvest, which is based on Twitter API, to collect tweets containing relevant keywords during the period from March to May of 2025. Subsequently, the collected data underwent processing and classification into three sentiment categories: positive, negative, and neutral. This classification was achieved through the utilization of the Orange Data Mining application, in conjunction with the findings derived from Drone Emprit. The results of the sentiment analysis of tweets related to Dedi Mulyadi revealed that neutral sentiment constituted 78.7% of the total, positive sentiment 17.2%, and negative sentiment 4.1%. The sentiments expressed in the tweets pertained to Dedi Mulyadi's performance, daily life, and programs. Preliminary findings from the analysis indicate a positive-neutral sentiment trend on platform X. This phenomenon can be attributed to the predominance of reposter accounts in conversations related to Dedi Mulyadi on X. Nevertheless, these findings demonstrate that leadership in the digital era is not solely influenced by virtual narratives and real actions on the ground, but also by the translation and perception of these actions by the digital society. This research lends further credence to the notion that social media has emerged as a significant instrument for the monitoring of public opinion.